Sclerostin injection enhances orthodontic tooth movement in rats. (March 2019) - Lu, Wenxin; Zhang, Xuan; Firth, Fiona; Mei, Li; Yi, Jianru; Gong, Changyang; Li, Hanshi; Zheng, Wei; Li, Yu
Highlights: The injection of sclerostin protein could accelerate orthodontic tooth movement. The injection of sclerostin protein increased osteoclastogenesis on the compression side. No inhibition of osteogenesis was observed on the tension side. Abstract: Objective: It was aimed to investigate the in vivo effects of local injection of sclerostin protein on orthodontic tooth movement. Design: A total of 48 rats underwent orthodontic mesialization of the maxillary first molars on both sides. Local injection was given at the compression side in the alveolar bone on both maxillary sides, with sclerostin protein carried by hydrogel on one side, and the same volume of normal saline carried by hydrogel on the other side serving as the control. After two weeks, the tooth movement amount and effects on the periodontium were assessed through micro-computed tomography (μCT) analysis, tartrate-resistant acid phosphatase (TRAP) staining and immunohistochemistry (IHC) analysis. Results: After two weeks of intervention, tooth movement was significantly greater in the 4 μg/kg and 20 μg/kg sclerostin injection groups, compared to the control. Analysis of the furcation area of the maxillary first molar showed that the 20 μg/kg group had significantly decreased BV/TV. At the compression side, the number of TRAP-positive osteoclasts was significantly increased in 20 μg/kg group compared to the control. The expression of RANKL was statistically higher in all the sclerostin groups, while the expression of OPG was statistically lower in the 4 μg/kg and 20 μg/kg groups, compared to the control. At the tension side, the expression of RUNX2 and COL-1 was statistically higher in the 20 μg/kg group compared to the control. Conclusions: Local injection of sclerostin protein in the alveolar bone at the compression side accelerates OTM in rats by promoting osteoclastogenesis.